Deformation behavior and strengthening effects of an eutectic AlCoCrFeNi2.1 high entropy alloy probed by in-situ synchrotron X-ray diffraction and post-mortem EBSD - Shen, Jiajia (2023)
Funding Information: JS, JGL, and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394). JGL acknowledges FCT – MCTES for funding the Ph.D. grant 2020.07350.BD. JPO acknowledges funding by national funds from FCT - Fundação para a Ciência e a Tecnologia, I.P. in the scope of the projects LA/P/0037/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication – i3N. The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872from the EU Framework Programme for Research and Innovation HORIZON 2020. HSK acknowledges the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIP) (NRF-2021R1A2C3006662, NRF-2022R1A5A1030054). Yeon Taek Choi was supported by the Basic Science Research Program “Fostering the Next Generation of Researcher” through the NRF funded by the Ministry of Education [grant number 2022R1A6A3A13073824]. The raw/processed data required to reproduce the above findings cannot be shared at this time as the data also forms part of an ongoing study. Publisher Copyright: © 2023 The Authors